2007
DOI: 10.1111/j.1365-2257.2006.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticulocyte haemoglobin content vs. soluble transferrin receptor and ferritin index in iron deficiency anaemia accompanied with inflammation

Abstract: Ferritin concentration, as a parameter of iron status that is commonly used in the diagnosis of iron deficiency anaemia (IDA), often has limited values if the iron deficiency is accompanied by inflammatory disease. This study evaluated the value of reticulocyte haemoglobin content (CHr) and soluble transferrin receptor-ferritin index (sTfR/F) in the diagnosis of IDA and differential diagnosis of IDA and anaemia of chronic disease. The study included 66 nonanaemic individuals as controls, 86 patients with IDA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 19 publications
3
36
1
2
Order By: Relevance
“…The increase in hepcidin concentration caused by inflammation leads to a reduction in overall iron availability [17], and it might reduce the amount of iron in the reticulocytes and thus the Ret-H e values. This hypothesis is speculative, since current evidence suggests that Ret-H e does not seem to be affected by inflammation [18,19,20] and therefore has advantages over other iron status parameters such as ferritin. In contrast, a small observational study seems to support the abovementioned hypothesis: it demonstrated that patients with community-acquired pneumonia and initially elevated CRP and hepcidin levels showed a decrease in Ret-H e within 4 days of admission [21].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in hepcidin concentration caused by inflammation leads to a reduction in overall iron availability [17], and it might reduce the amount of iron in the reticulocytes and thus the Ret-H e values. This hypothesis is speculative, since current evidence suggests that Ret-H e does not seem to be affected by inflammation [18,19,20] and therefore has advantages over other iron status parameters such as ferritin. In contrast, a small observational study seems to support the abovementioned hypothesis: it demonstrated that patients with community-acquired pneumonia and initially elevated CRP and hepcidin levels showed a decrease in Ret-H e within 4 days of admission [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reticulocyte Hb content (CHr) is an early, sensitive indicator of a favorable response to iron administration. [97][98][99] The concomitant administration of ascorbic acid enhances iron absorption. In some of our patients, serine ferrous sulfate and ferrous glycine sulfate elicited good responses when other iron preparations failed, but the relative advantage of these preparations still awaits objective evaluation by prospective randomized trials.…”
Section: Oral Iron Therapymentioning
confidence: 99%
“…Among the available reticulocyte indices, reticulocyte haemoglobin content (CHr) is the most promising and several attempts have been made to assess its performance in this context. Although different definitions of iron deficiency and iron deficiency anaemia have been applied, several studies have focused on assessing diagnostic accuracy of CHr in diagnosing these two clinical conditions [8,9,17]. However, exploring the diagnostic capabilities of CHr and other reticulocyte indices in these clinical situations is a far more complex issue in countries with high prevalence of hereditary microcytic anaemias such as the haemoglobinopathies, due to the effect of the latter on the indices of erythropoiesis [6].…”
Section: Introductionmentioning
confidence: 99%